2002
DOI: 10.1080/01902140290103062
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Phorbol Ester on the Regulation of Amiloride-Sensitive Epithelial Sodium Channel in Alveolar Type Ii Epithelial Cells

Abstract: Amiloride-sensitive sodium channel (ENaC) plays an important role in recovery from pulmonary edema. Recently, it has been shown that an activation of protein kinase C (PKC) could affect the mRNA expression of ENaC in rat parotid gland cells and A6 distal nephron epithelial cells. To determine whether an activation of PKC would regulate the mRNA expression or the function of ENaC, we stimulated rat alveolar type II epithelial cells with phorbol 12-myristate 13-acetate (PMA), a potent PKC activator, at a concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…These data indicate that PKC activation rather than depletion is involved in this process. Our results are similar to what has been noted in other epithelial cells (Zentner et al 1998;Stockand et al 2000;Yamagata et al 2002;Booth and Stockand 2003), in which the expression of either α, β, or γENaC is modulated by PMA.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These data indicate that PKC activation rather than depletion is involved in this process. Our results are similar to what has been noted in other epithelial cells (Zentner et al 1998;Stockand et al 2000;Yamagata et al 2002;Booth and Stockand 2003), in which the expression of either α, β, or γENaC is modulated by PMA.…”
Section: Discussionsupporting
confidence: 94%
“…Recently, Yamagata et al (2002) reported that 24-h treatment of alveolar epithelial cells decreases ENaC expression and function. Their study focused only on the impact of 24-h treatment with PMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 5 days, untreated epithelia showed a resistance of 1276 Ϯ 46 ⍀.cm 2 (p Ͻ0.01 compared with phorbol 12-myristate 13-acetate). However, phorbol 12-myristate 13-acetate has been shown to decrease amiloride-sensitive sodium currents, and thus we cannot conclude that the increase in Rt is solely due to an effect on the paracellular pathway (18).…”
Section: Unphosphorylated Pp2a Is Associated With Tight Junction Protmentioning
confidence: 76%
“…We postulated that ENaC may be the ultimate downstream target of (c)PKC. This view is based on several studies that showed a reduction in ENaC expression following exposure to PMA (1,7,37). Our model is somewhat different: we are looking at the acute functional effect of PKC activation, while most previous studies focused on longer-term downregulation of ENaC mRNA.…”
Section: Discussionmentioning
confidence: 99%